Hak Nafkah Isteri (Perspektif Hadis dan Kompilasi Hukum Islam) - Hudaya, Hairul (IAIN Antasari Banjarmasin, 2013)
Hadith, as a second source of Islamic laws after the Qurâan, contains various provisions of the laws, including the rights of wifes livelihood. Meanwhile, in the context of law in Indonesia, Compilation of Islamic Laws is used as the legal basis in settling lawsuits in Religious Courts. The Compilation of Islamic Laws is compiled with considering the moeslem scholars thought especially they who adhere to al-Syafiâi notion. The theologians themselves are oriented to the Qurâan and Hadith in defining laws. Then, are there any differences between the laws products in the Compilation of Islamic Laws and the source of Islamic laws especially hadith concerning livelihood issues? It is found that the difference is when the wifes commit nusyuz, their reights will be eliminated. The notion is more likely based on the scholars judgement and it is not clearly elaborated in the Hadith.